The ASPREE Healthy Ageing Biobank: Methodology and participant characteristics. - Emily J Parker; Suzanne G Orchard; Tom J Gilbert; James J Phung; Alice J Owen; Trevor Lockett; Mark R Nelson; Christopher M Reid; Andrew M Tonkin; Walter P Abhayaratna; Peter Gibbs; John J McNeil; et al. (PLoS ONE, 2024)
ASPirin in Reducing Events in the Elderly (ASPREE), a placebo-controlled prevention trial of low dose aspirin, provided the opportunity to establish a biospecimen biobank from initially healthy persons aged 70+ years for future research. The ASPREE Healthy Ageing Biobank (ASPREE Biobank) collected, processed and stored blood and urine samples at -80degC or under nitrogen vapour at two timepoints, three years apart, from a willing subset of Australian ASPREE participants. Written informed consent included separate opt-in questions for biomarker and genetic testing. Fractionated blood and urine were aliquoted into multiple low-volume, barcoded cryotubes for frozen storage within 4 hours of collection. Specially designed and outfitted mobile laboratories provided opportunities for participation by people in regional and rural areas. Detailed, high quality demographic, physiological and clinical data were collected annually through the ASPREE trial. 12,219 participants contributed blood/urine at the first timepoint, 10,617 of these older adults provided 3-year follow-up samples, and an additional 1,712 provided saliva for DNA. The mean participant age was 74 years, 54% were female and 46% lived outside major cities. Despite geographical and logistical challenges, nearly 100% of blood/urine specimens were processed and frozen within 4 hours of collection into >1.4 million aliquots. After a median of 4.7 years, major clinical events among ASPREE Biobank participants included 332 with dementia, 613 with cardiovascular disease events, 1259 with cancer, 357 with major bleeds and 615 had died. The ASPREE Biobank houses and curates a large number of biospecimens collected prior to the clinical manifestations of major disease, and 3-year follow-up samples, all linked to high quality, extensive phenotypic information. This provides the opportunity to identify or validate diagnostic, prognostic and predictive biomarkers, and potentially study biological effectors, of ageing-related diseases or maintenance of older-age good health.